Fighting terrorism in Africa: Complementarity between inclusive development, military expenditure and political stability - Simplice Asongu; Sara Le Roux; Pritam Singh (African Governance and Development Institute (AGDI), 2020)
This study examines complementarities between inclusive development, military expenditure and political stability in the fight against terrorism in 53 African countries for the period 1998-2012. Hence the policy variables employed in the study are inclusive development, military expenditure and political stability. The empirical evidence is based on Generalised Method of Moments (GMM) with forward orthogonal deviations. The paper reports three main findings. Firstly, military expenditure and inclusive development are substitutes and not complements. Secondly, it is more relevant to use political stability as a complement of inclusive development than to use inclusive development as a complement of political stability. Thirdly, it can be broadly established that military expenditure and political stability are complementary. In the light of the sequencing, complementarity and substitutability, when the three policy variables are viewed within the same framework, it is more feasible to first pursue political stability and then complement it with military expenditure and inclusive development.
Keywords: C52; D74; F42; O16; O38; 330; Terrorism; Inclusive development; Political stability; Military expenditure; Africa